2006
DOI: 10.1093/auk/123.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Habitat Preferences of Gray Vireos (Vireo Vicinior) on the Colorado Plateau

Abstract: The Gray Vireo (Vireo vicinior; hereafter “vireo”) is a little-studied songbird with small breeding and wintering ranges. Because of uncertainty about vireo populations, conservationists are concerned about the future of this species. The goal of the present study was to provide new data on the ecology of the vireo to help determine its conservation status. During May and June 2001, I studied breeding habitat selection by vireos on the Colorado Plateau in northern Arizona and southern Utah. I surveyed for vire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 15 publications
2
18
1
1
Order By: Relevance
“…Monitoring efforts have increased in some areas (Walker and Doster ), but trends are unclear and populations appear to be highly patchy and discontinuous throughout the range. For example, Gray Vireos were observed in only 17% of atlas blocks in Arizona from 1993 to 2000 (Corman ), only 94 birds were detected at 282 points on the Colorado Plateau of Arizona and Utah in 2001 (Schlossberg ), and the estimated total population at 49 known sites in New Mexico ranged from 549 to 827 birds in 2005 (DeLong and Williams ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring efforts have increased in some areas (Walker and Doster ), but trends are unclear and populations appear to be highly patchy and discontinuous throughout the range. For example, Gray Vireos were observed in only 17% of atlas blocks in Arizona from 1993 to 2000 (Corman ), only 94 birds were detected at 282 points on the Colorado Plateau of Arizona and Utah in 2001 (Schlossberg ), and the estimated total population at 49 known sites in New Mexico ranged from 549 to 827 birds in 2005 (DeLong and Williams ).…”
Section: Discussionmentioning
confidence: 99%
“…Such nest sites could help deter both scrub‐jays and cowbirds by reducing the number of nearby perches from which a nest is more likely to be visible (Sharp and Kus ). In other parts of the range, nest‐site selection has not been studied, but Schlossberg () found that Gray Vireo territories were associated with less pinyon and more juniper mixed with other shrubs, especially sagebrush ( Artemisia tridentata ). However, in pinyon‐juniper in New Mexico, Johnson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to other southwestern vireos, Gray Vireos (Vireo vicinior) are understudied in many aspects of their life-history (Barlow et al 1999, Schlossberg 2006. Gray Vireos are migratory with a breeding range that includes New Mexico, Colorado, Arizona, Utah, and small populations in California, Nevada, and Texas (Barlow et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hardy (1945) and Short and McCulloch (1977) described juniper as a preferred nesting substrate; however, few data were presented in these reports. Cicero (2000) reported that the juniper titmouse ( Baeolophus ridgwayi ) is more common where juniper is the dominant tree and Schlossberg (2006) found that gray vireo ( Vireo vicinior ) densities increase as juniper becomes more prevalent than piñon, yet neither of these studies described nest substrate use.…”
Section: Discussionmentioning
confidence: 99%